The Impact of Heating Systems on Society and Nature: New Opportunities Based on Blockchain Technology - Dinu, Daniel Gabriel; Mihoreanu, Larisa; Stoian Karadeli, Andreea (Journal of Economic Development, Environment and People, 2023)
The paper assesses the importance of the models used to determine the efficiency and the environmental impact of the heating products like heating pumps (HP). An appropriate model of evaluation may help identifying the presence of greenhouse gases and reducing their influence. The paper's novelty resides in the way the hidden sides linked to greenhouse gases' presence, are identified, and eliminated. The research methodology considers an environmental model linked both to the Global Emission Model for Integrated Systems on energy efficiency indicators and to the break-even analysis for greenhouse gases. The model gives hints on reducing the high costs to upgrade the living conditions in residential buildings. The results illustrate the environmental and societal impact and the social potential and highlight the technical implications for such operating systems. They incite optimizing the Heat Hybrid Pumps' design within decentralized energy systems to strengthen energy networks' flexibility and the environmental convenience. The research straightens out the understanding of heat pumps mechanisms, delineates the efficiency of their increasing use through the block-chain technology outlining its future potential for people and society's health and benefit.